Epidemiology of Sudden Death in a Population-Based Study of Infants and Children - Kristin M. Burns, MD; Carri Cottengim, MA; Heather Dykstra, MPA; Meghan Faulkner, MA; Alexa B. Erck Lambert, MPH; Heather MacLeod, MS CGC; Alissa Novak, BSc; Sharyn E. Parks, PhD, MPH; Mark W. Russell, MD; Carrie K. Shapiro-Mendoza, PhD, MPH; Esther Shaw, MSIS; Niu Tian, MD, PhD; et al. (Elsevier, 2020)
Objective: To describe epidemiologic data from the Sudden Death in the Young (SDY) Case Registry. Understanding the scope of SDY may optimize prevention efforts. Study design: We analyzed sudden, unexpected deaths of infants (<365 days) and children (1-17 years) from a population-based registry of 8 states/jurisdictions in 2015 and 9 in 2016. Natural deaths and injury deaths from drowning, motor vehicle accident drivers, and infant suffocation were included; other injury deaths, homicide, suicide, intentional overdose, and terminal illness were excluded. Cases were categorized using a standardized algorithm. Descriptive statistics were used to characterize deaths, and mortality rates were calculated. Results: Of 1319 cases identified, 92% had an autopsy. We removed incomplete cases, leaving 1132 analyzable deaths (889 infants, 243 children). The SDY rate for infants was 120/100 000 live births and for children was 1.9/100 000 children. Explained Cardiac rates were greater for infants (2.7/100 000 live births) than children (0.3/100 000 children). The pediatric Sudden Unexpected Death in Epilepsy (SUDEP) mortality rate was 0.2/100 000 live births and children. Blacks comprised 42% of infant and 43% of child deaths but only 23% of the population. In all ages, myocarditis/endocarditis was the most common Explained Cardiac cause; respiratory illness was the most common Explained Other cause. SDY occurred during activity in 13% of childhood cases. Conclusions: Prevention strategies include optimizing identification and treatment of respiratory and cardiac diseases.